2014
DOI: 10.2147/ijwh.s47074
|View full text |Cite
|
Sign up to set email alerts
|

The value of 3D and 4D assessments of the fetal heart

Abstract: The objective of this review was to demonstrate the main tools of three- and four-dimensional ultrasonography, using the spatiotemporal image correlation software and its respective applications for assessing the fetal heart and its vascular connections, along with its potential contribution towards screening for congenital heart diseases. Today, conventional, two-dimensional, echocardiography continues to be the gold standard for diagnosing congenital heart diseases. However, recent studies have demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Moreover, five ‘short‐axis views’ have been proposed as a screening method for comprehensive fetal echocardiography. A large body of evidence now indicates that four‐dimensional (4D) sonography with spatiotemporal image correlation (STIC) can facilitate examination of the fetal heart and may also be used to evaluate CHD. STIC technology enables acquisition of a volume dataset of the fetal heart, and displays a cine loop of a complete, single cardiac cycle in motion.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, five ‘short‐axis views’ have been proposed as a screening method for comprehensive fetal echocardiography. A large body of evidence now indicates that four‐dimensional (4D) sonography with spatiotemporal image correlation (STIC) can facilitate examination of the fetal heart and may also be used to evaluate CHD. STIC technology enables acquisition of a volume dataset of the fetal heart, and displays a cine loop of a complete, single cardiac cycle in motion.…”
Section: Introductionmentioning
confidence: 99%
“…These challenges in prenatal diagnosis might generally be attributed to the complex anatomy of the heart, its motion, and its relatively small size . Four‐dimensional ultrasound (US) with spatiotemporal image correlation (STIC) has been shown to be able to overcome these issues . Nevertheless, the detailed information incorporated in an STIC volume is rather difficult to depict, mainly because of operator dependency and lack of standardization .…”
mentioning
confidence: 99%
“…In addition, the calculated reference range for the fetal interventricular septum has been found to correlate with gestational age (r 5 0.81) and to increase from 0.47 cm 2 at 18 wk to 2.42 cm 2 at 33 wk of gestation, respectively ). Very recently, Araujo J unior et al (2014b) reported that 4-D fetal echocardiography in the rendering mode allows visualization of the virtual planes of the interatrial and interventricular septa and of the atrioventricular valve annulus.…”
Section: -Dus and Fetal Echocardiogrammentioning
confidence: 99%